Psychometric test of the Team Climate Inventory-short version investigated in Dutch quality improvement teams - Nieboer Anna P; Strating Mathilde MH (BMC, 2009)
Abstract Background Although some studies have used the Team Climate Inventory within teams working in health care settings, none of these included quality improvement teams. The aim of our study is to investigate the psychometric properties of the 14-item version of the Team Climate Inventory in healthcare quality improvement teams participating in a Dutch quality collaborative. Methods This study included quality improvement teams participating in the Care for Better improvement program for home care, care for the handicapped and the elderly in the Netherlands between 2006 and 2008. As part of a larger evaluation study 270 written questionnaires from team members were collected at baseline and 139 questionnaires at end measurement. Confirmatory factor analyses, reliability, Pearson correlations and paired samples t-tests were conducted to investigate construct validity, reliability, predictive validity and temporal stability. Results Confirmatory factor analyses revealed the expected four-factor structure and good fit indices. For the four subscales - vision, participative safety, task orientation and support for innovation - acceptable Cronbach's alpha coefficients and high inter-item correlations were found. The four subscales all proved significant predictors of perceived team effectiveness, with participatory safety being the best predictor. As expected the four subscales were found to be stable over time; i.e. without significant changes between baseline and end measurement. Conclusion The psychometric properties of the Dutch version of the TCI-14 are satisfactory. Together these results show that the TCI-14 is a useful instrument to assess to what extent aspects of team climate influence perceived team effectiveness of quality improvement teams.